Complete mitochondrial genome of Laqueus Japonicus (Brachiopoda, Terebratulida, Laqueidae) - Karagozlu, Mustafa Zafer (Mitochondrial DNA B Resour, 2017)
In this study a complete mitochondrial genome of the species, Laqueus japonicus was sequenced and analysed. The mitochondrial genome size is 14,267 bp with 20.2% A, 15.7% C, 27.1% G, and 37.0% T nucleotide distributions. This is the second complete mitochondrial genome record from the genus Laqueus and first record for the species. Genome structure and gene orientation are identical with previous record of the genus. In addition, phylogenetic relationship of L. japonicus in the subphylum Rhynchonelliformea was investigated by using protein coding genes of complete mitochondrial genome. The present study suggests that the closest species to L. japonicus is L. rubellus and they belong to the family Laqueidae.